Ants as bioindicators of riparian ecological health in catalonian rivers - Zina, Vera (2021)
In this study, we assess the potential of ants as bioindicators of riparian ecological health in two river types (upland and lowland type) located in the Catalonian region. We proposed to understand to what extent do metrics based on ant responses provide useful information that cannot be presented by traditional biophysical assessments while attempting an approach to creating an ant-based multimetric index (ant-based MMI) of the riparian ecological health. A total of 22 ant species were identified, and 42 metrics related to ant foraging activity, species richness, and functional traits were evaluated as potential core metrics of the index. Riparian features and proximal land use land cover (LULC) were used to distinguish disturbed from less disturbed sites. We found that ant communities strongly responded to human disturbance. When compared with an exclusively physical-based index for the assessment of the riparian health, the ant-based MMI was more sensitive to human disturbance, by also reacting to the effects of the surrounding LULC pressure. This study provides a preliminary approach for an ant-based assessment tool to evaluate the health of riparian corridors although additional research is required to include other river types and a wider stressor gradient before a wider application